Drug delivery, biodistribution and anti-EGFR activity: theragnostic nanoparticles for simultaneous in vivo delivery of tyrosine kinase inhibitors and kinase activity biosensors. Issue 44 (3rd November 2021) - Bofinger, Robin; Weitsman, Gregory; Evans, Rachel; Glaser, Matthias; Sander, Kerstin; Allan, Helen; Hochhauser, Daniel; Kalber, Tammy L.; Årstad, Erik; Hailes, Helen C.; Ng, Tony; Tabor, Alethea B.
Abstract : We report the development of targeted theragnostic lipid/peptide/DNA lipopolyplexes for delivery of both a tyrosine kinase inhibitor, and plasmid DNA coding for a biosensor. These are used to quantify EGFR inhibition in cancer cell lines in vivo . Abstract : In vivo delivery of small molecule therapeutics to cancer cells, assessment of the selectivity of administration, and measuring the efficacity of the drug in question at the molecule level, are important ongoing challenges in developing new classes of cancer chemotherapeutics. One approach that has the potential to provide targeted delivery, tracking of biodistribution and readout of efficacy, is to use multimodal theragnostic nanoparticles to deliver the small molecule therapeutic. In this paper, we report the development of targeted theragnostic lipid/peptide/DNA lipopolyplexes. These simultaneously deliver an inhibitor of the EGFR tyrosine kinase, and plasmid DNA coding for a Crk-based biosensor, Picchu-X, which when expressed in the target cells can be used to quantify the inhibition of EGFR in vivo in a mouse colorectal cancer xenograft model. Reversible bioconjugation of a known analogue of the tyrosine kinase inhibitor Mo-IPQA to a cationic peptide, and co-formulation with peptides containing both EGFR-binding and cationic sequences, allowed for good levels of inhibitor encapsulation with targeted delivery to LIM1215 colon cancer cells. Furthermore, high levels of expression of the Picchu-X biosensor in the LIM1215 cells in vivo allowed us to demonstrate, using fluorescence lifetime microscopy (FLIM)-based biosensing, that EGFR activity can be successfully suppressed by the tyrosine kinase inhibitor, released from the lipopolyplexes. Finally, we measured the biodistribution of lipopolyplexes containing 125 I-labelled inhibitors and were able to demonstrate that the lipopolyplexes gave significantly higher drug delivery to the tumors compared with free drug.